Improving the Airport Customer Experience - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
TRB's Airport Cooperative Research Program (ACRP) Report 157: Improving the Airport Customer Experience documents notable and emerging practices in airport customer service management that increase customer satisfaction, recognizing the different types of customers (such as passengers, meeters and greeters, and employees) and types and sizes of airports. It also identifies potential improvements that airports could make for their customers.

Quality in the Undergraduate Experience: What Is It? How Is It Measured? Who Decides? Summary of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Students, parents, and government agencies need as much information as possible about the outcomes of the higher education experience and the extent to which they can expect a fair return on their investment in higher education.In order to better understand the concept of quality - enabling students to acquire knowledge in a variety of disciplines and deep knowledge in at least one discipline, as well as to develop a range of skills and habits of mind that prepare them for career success, engaged citizenship, intercultural competence, social responsibility, and continued intellectual growth - an ad hoc planning committee of the National Academies of Sciences, Engineering, and Medicine Board on Higher Education and Workforce, with funding from the Lumina Foundation, organized a workshop in Washington, D.C., on December 14-15, 2015.This report summarizes the presentations and discussion of that event.

Ending Discrimination Against People with Mental and Substance Use Disorders: The Evidence for Stigma Change - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Estimates indicate that as many as 1 in 4 Americans will experience a mental health problem or will misuse alcohol or drugs in their lifetimes. These disorders are among the most highly stigmatized health conditions in the United States, and they remain barriers to full participation in society in areas as basic as education, housing, and employment. Improving the lives of people with mental health and substance abuse disorders has been a priority in the United States for more than 50 years. The Community Mental Health Act of 1963 is considered a major turning point in America's efforts to improve behavioral healthcare. It ushered in an era of optimism and hope and laid the groundwork for the consumer movement and new models of recovery. The consumer movement gave voice to people with mental and substance use disorders and brought their perspectives and experience into national discussions about mental health. However over the same 50-year period, positive change in American public attitudes and beliefs about mental and substance use disorders has lagged behind these advances. Stigma is a complex social phenomenon based on a relationship between an attribute and a stereotype that assigns undesirable labels, qualities, and behaviors to a person with that attribute. Labeled individuals are then socially devalued, which leads to inequality and discrimination. This report contributes to national efforts to understand and change attitudes, beliefs and behaviors that can lead to stigma and discrimination. Changing stigma in a lasting way will require coordinated efforts, which are based on the best possible evidence, supported at the national level with multiyear funding, and planned and implemented by an effective coalition of representative stakeholders. Ending Discrimination Against People with Mental and Substance Use Disorders: The Evidence for Stigma Change explores stigma and discrimination faced by individuals with mental or substance use disorders and recommends effective strategies for reducing stigma and encouraging people to seek treatment and other supportive services. It offers a set of conclusions and recommendations about successful stigma change strategies and the research needed to inform and evaluate these efforts in the United States.

Transit Agency Practices in Interacting with People Who Are Homeless - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
TRB's Transit Cooperative Research Program (TCRP) Synthesis 121: Transit Agency Practices in Interacting with People Who Are Homeless reports on effective practices, approaches, and outcomes regarding interactions within the transit industry with people who are homeless. A literature review summarizes policies and practices used in both the transit and library communities. Because public libraries are similar to public transportation in offering services to all members of the general public and in being viewed as a safe haven for people who are homeless, the literature review includes an examination of library policies and procedures related to people who are homeless.

Use of Taxis in Public Transportation for People with Disabilities and Older Adults - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
TRB's Transit Cooperative Research Program (TCRP) Synthesis 119: Use of Taxis in Public Transportation for People with Disabilities and Older Adults explores and summarizes how taxis may be used by public transportation agencies to provide disabled or older adults with greater mobility and access to their destinations. The report also identifies potential advantages and challenges that public transportation agencies may face when using taxis.

Lessons Learned From the Fukushima Nuclear Accident: Two Volume Set (The National Academies Press, 2016)

Highway Capacity Manual 6th Edition: A Guide for Multimodal Mobility Analysis - Transportation Research Board (The National Academies Press, 2016)
Now available to order from the TRB Bookstore, the Highway Capacity Manual, Sixth Edition: A Guide for Multimodal Mobility Analysis (HCM) provides methods for quantifying highway capacity. In its current form, it serves as a fundamental reference on concepts, performance measures, and analysis techniques for evaluating the multimodal operation of streets, highways, freeways, and off-street pathways. The Sixth Edition incorporates the latest research on highway capacity, quality of service, Active Traffic and Demand Management, and travel time reliability and improves the HCM's chapter outlines. The objective is to help practitioners applying HCM methods understand their basic concepts, computational steps, and outputs. These changes are designed to keep the manual in step with its users' needs and present times. HCM has evolved over the years to keep pace with the needs of its users and society, as the focus of surface transportation planning and operations in the United States has moved from designing and constructing the Interstate highway system to managing a complex transportation system that serves a variety of users and travel modes. Providing mobility for people and goods is transportation's most essential function. It consists of four dimensions: Quantity of travel, the magnitude of use of a transportation facility or service; Quality of travel, users' perceptions of travel on a transportation facility or service with respect to their expectations; Accessibility, the ease with which travelers can engage in desired activities; and Capacity, the ability of a transportation facility or service to meet the quantity of travel demanded of it. Notice to current Examiners of the Fundamentals of Engineering (FE) Exam and the Principles and Practice of Engineering (PE) Exam: Current versions of these exams are based on the Highway Capacity Manual 2010 (HCM2010) which is available in the TRB store. Future updates of the exam based on HCM6 are in review by the accreditation agency and will be noted on the TRB website.

Nutrient Requirements of Beef Cattle: Eighth Revised Edition - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Since 1944, the National Research Council (NRC) has published seven editions of the Nutrient Requirements of Beef Cattle. This reference has guided nutritionists and other professionals in academia and the cattle and feed industries in developing and implementing nutritional and feeding programs for beef cattle. The cattle industry has undergone considerable changes since the seventh revised edition was published in 2000 and some of the requirements and recommendations set forth at that time are no longer relevant or appropriate. The eighth revised edition of the Nutrient Requirements of Beef Cattle builds on the previous editions. A great deal of new research has been published during the past 14 years and there is a large amount of new information for many nutrients. In addition to a thorough and current evaluation of the literature on the energy and nutrient requirements of beef in all stages of life, this volume includes new information about phosphorus and sulfur contents; a review of nutritional and feeding strategies to minimize nutrient losses in manure and reduce greenhouse gas production; a discussion of the effect of feeding on the nutritional quality and food safety of beef; new information about nutrient metabolism and utilization; new information on feed additives that alter rumen metabolism and postabsorptive metabolism; and future areas of needed research. The tables of feed ingredient composition are significantly updated. Nutrient Requirements of Beef Cattle represents a comprehensive review of the most recent information available on beef cattle nutrition and ingredient composition that will allow efficient, profitable, and environmentally conscious beef production.

Lessons Learned from the Fukushima Nuclear Accident for Improving Safety and Security of U.S. Nuclear Plants: Phase 2 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
The U.S. Congress asked the National Academy of Sciences to conduct a technical study on lessons learned from the Fukushima Daiichi nuclear accident for improving safety and security of commercial nuclear power plants in the United States. This study was carried out in two phases: Phase 1, issued in 2014, focused on the causes of the Fukushima Daiichi accident and safety-related lessons learned for improving nuclear plant systems, operations, and regulations exclusive of spent fuel storage. This Phase 2 report focuses on three issues: (1) lessons learned from the accident for nuclear plant security, (2) lessons learned for spent fuel storage, and (3) reevaluation of conclusions from previous Academies studies on spent fuel storage.

Parenting Matters: Supporting Parents of Children Ages 0-8 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Decades of research have demonstrated that the parent-child dyad and the environment of the family2014which includes all primary caregivers2014are at the foundation of children's well- being and healthy development. From birth, children are learning and rely on parents and the other caregivers in their lives to protect and care for them. The impact of parents may never be greater than during the earliest years of life, when a child's brain is rapidly developing and when nearly all of her or his experiences are created and shaped by parents and the family environment. Parents help children build and refine their knowledge and skills, charting a trajectory for their health and well-being during childhood and beyond. The experience of parenting also impacts parents themselves. For instance, parenting can enrich and give focus to parents' lives; generate stress or calm; and create any number of emotions, including feelings of happiness, sadness, fulfillment, and anger. Parenting of young children today takes place in the context of significant ongoing developments. These include: a rapidly growing body of science on early childhood, increases in funding for programs and services for families, changing demographics of the U.S. population, and greater diversity of family structure. Additionally, parenting is increasingly being shaped by technology and increased access to information about parenting. Parenting Matters identifies parenting knowledge, attitudes, and practices associated with positive developmental outcomes in children ages 0-8; universal\/preventive and targeted strategies used in a variety of settings that have been effective with parents of young children and that support the identified knowledge, attitudes, and practices; and barriers to and facilitators for parents' use of practices that lead to healthy child outcomes as well as their participation in effective programs and services. This report makes recommendations directed at an array of stakeholders, for promoting the wide-scale adoption of effective programs and services for parents and on areas that warrant further research to inform policy and practice. It is meant to serve as a roadmap for the future of parenting policy, research, and practice in the United States.

Summertime Opportunities to Promote Healthy Child and Adolescent Development: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
What children and adolescents do and learn in the summertime can have profound effects on their health and well-being, educational attainment, and career prospects. To explore the influence of summertime activities on the lives of young people, the National Academies of Sciences, Engineering, and Medicine held a workshop in August 2016. The participants discussed a wide range of topics, including the value of play, healthy eating and physical activity, systemic approaches to skill development, program quality and measurement, and the interconnected ecosystem of activities that supports healthy development. The workshop highlighted the latest research on summer programming, as well as gaps in that research, and explored the key policy and practice issues for summertime opportunities to promote healthy child and adolescent development. This publication briefly summarizes the presentations and discussions from the workshop.

Science Literacy: Concepts, Contexts, and Consequences - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Science is a way of knowing about the world. At once a process, a product, and an institution, science enables people to both engage in the construction of new knowledge as well as use information to achieve desired ends. Access to science2014whether using knowledge or creating it2014necessitates some level of familiarity with the enterprise and practice of science: we refer to this as science literacy. Science literacy is desirable not only for individuals, but also for the health and well- being of communities and society. More than just basic knowledge of science facts, contemporary definitions of science literacy have expanded to include understandings of scientific processes and practices, familiarity with how science and scientists work, a capacity to weigh and evaluate the products of science, and an ability to engage in civic decisions about the value of science. Although science literacy has traditionally been seen as the responsibility of individuals, individuals are nested within communities that are nested within societies2014and, as a result, individual science literacy is limited or enhanced by the circumstances of that nesting. Science Literacy studies the role of science literacy in public support of science. This report synthesizes the available research literature on science literacy, makes recommendations on the need to improve the understanding of science and scientific research in the United States, and considers the relationship between scientific literacy and support for and use of science and research.

Advancing Health Equity for Native American Youth: Workshop Summary - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
More than 2 million Americans below age 24 self-identify as being of American Indian or Alaska Native descent. Many of the serious behavioral, emotional, and physical health concerns facing young people today are especially prevalent with Native youth (e.g., depression, violence, and substance abuse). Adolescent Native Americans have death rates two to five times the rate of whites in the same age group because of higher levels of suicide and a variety of risky behaviors (e.g., drug and alcohol use, inconsistent school attendance). Violence, including intentional injuries, homicide, and suicide, accounts for three-quarters of deaths for Native American youth ages 12 to 20. Suicide is the second leading cause of death2014and 2.5 times the national rate2014for Native youth ages 15 to 24. Arrayed against these health problems are vital cultural strengths on which Native Americans can draw. At a workshop held in 2012, by the National Academies of Sciences, Engineering, and Medicine, presenters described many of these strengths, including community traditions and beliefs, social support networks, close-knit families, and individual resilience. In May 2014, the Academies held a follow-up workshop titled Advancing Health Equity for Native American Youth. Participants discussed issues related to (1) the visibility of racial and ethnic disparities in health and health care as a national problem, (2) the development of programs and strategies by and for Native and Indigenous communities to reduce disparities and build resilience, and (3) the emergence of supporting Native expertise and leadership. This report summarizes the presentations and discussions from the workshop.

Preventing Bullying Through Science, Policy, and Practice - National Academies of Sciences, Engineering,; Medicine
Bullying has long been tolerated as a rite of passage among children and adolescents. There is an implication that individuals who are bullied must have \

Art, Design and Science, Engineering and Medicine Frontier Collaborations: Ideation, Translation, Realization: Seed Idea Group Summaries (The National Academies Press, 2016)
Science and art were not always two separate entities. Historically, times of great scientific progress occurred during profound movements in art, the two disciplines working together to enrich and expand humanity's understanding of its place in this cosmos. Only recently has a dividing line been drawn, and this seeming dichotomy misses some of the fundamental similarities between the two endeavors. At the National Academies Keck Futures Initiative Conference on Art, Design and Science, Engineering and Medicine Frontier Collaborations: Ideation, Translation, and Realization, participants spent 3 days exploring diverse challenges at the interface of science, engineering, and medicine. They were arranged into Seed Groups that were intentionally diverse, to encourage the generation of new approaches by combining a range of different types of contributions. The teams included creative practitioners from the fields of art, design, communications, science, engineering, and medicine, as well as representatives from private and public funding agencies, universities, businesses, journals, and the science media.

Indo-U.S. Workshop on Challenges of Emerging Infections and Global Health Safety: Summary of a Workshop - National Academy of Sciences (The National Academies Press, 2016)
The United States and India have pledged to deepen the linkages between their people, their businesses, and their governments for the mutual benefit of both countries and for the promotion of global peace, stability, economic growth and prosperity. Both nations are now inclined to improve relations and cooperation, but the nations need specific actions that will yield progress and build confidence and momentum for further cooperation. The Indo-U.S. Workshop on Challenges of Emerging Infections and Global Health Safety, held in November 2014, encouraged scientists from both countries to examine global issues related to emerging and existing infections and global health safety, to share experience and approaches, and to identify opportunities for cooperation to improve practice and research in these areas. This report summarizes the presentations and discussions from the workshop.

Nutrition Across the Lifespan for Healthy Aging: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
On September 13-14, 2016, the National Academies of Sciences, Engineering, and Medicine's Food Forum convened a workshop in Washington, DC, to (1) examine trends and patterns in aging and factors related to healthy aging in the United States with a focus on nutrition; (2) examine how nutrition can sustain and promote healthy aging, not only in late adulthood, but beginning in pregnancy and early childhood and extending throughout the lifespan; (3) highlight the role of nutrition in the aging process at various stages in life; (4) discuss changes in organ systems over the lifespan, including the skeletal, muscular, and cardiovascular systems, and changes that occur with age related to cognitive, brain, and mental health; diet-related sensory preferences; oral health; and the microbiome; and (5) explore opportunities to move forward in promoting healthy aging in the United States. This Proceedings of a Workshop-in Brief summarizes key points of the workshop presentations and discussions. A comprehensive summary of the workshop will be publicly available in a forthcoming full-length Proceedings of a Workshop.

Speech and Language Disorders in Children: Implications for the Social Security Administration's Supplemental Security Income Program - Institute of Medicine; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Speech and language are central to the human experience; they are the vital means by which people convey and receive knowledge, thoughts, feelings, and other internal experiences. Acquisition of communication skills begins early in childhood and is foundational to the ability to gain access to culturally transmitted knowledge, organize and share thoughts and feelings, and participate in social interactions and relationships. Thus, speech disorders and language disorders2014disruptions in communication development2014can have wide-ranging and adverse impacts on the ability to communicate and also to acquire new knowledge and fully participate in society. Severe disruptions in speech or language acquisition have both direct and indirect consequences for child and adolescent development, not only in communication, but also in associated abilities such as reading and academic achievement that depend on speech and language skills. The Supplemental Security Income (SSI) program for children provides financial assistance to children from low-income, resource-limited families who are determined to have conditions that meet the disability standard required under law. Between 2000 and 2010, there was an unprecedented rise in the number of applications and the number of children found to meet the disability criteria. The factors that contribute to these changes are a primary focus of this report. Speech and Language Disorders in Children provides an overview of the current status of the diagnosis and treatment of speech and language disorders and levels of impairment in the U.S. population under age 18. This study identifies past and current trends in the prevalence and persistence of speech disorders and language disorders for the general U.S. population under age 18 and compares those trends to trends in the SSI childhood disability population.

Barriers and Opportunities for 2-Year and 4-Year STEM Degrees: Systemic Change to Support Students' Diverse Pathways - National Academy of Engineering; National Academies of Sciences, Engineering,; Medicine
Nearly 40 percent of the students entering 2- and 4-year postsecondary institutions indicated their intention to major in science, technology, engineering, and mathematics (STEM) in 2012. But the barriers to students realizing their ambitions are reflected in the fact that about half of those with the intention to earn a STEM bachelor's degree and more than two-thirds intending to earn a STEM associate's degree fail to earn these degrees 4 to 6 years after their initial enrollment. Many of those who do obtain a degree take longer than the advertised length of the programs, thus raising the cost of their education. Are the STEM educational pathways any less efficient than for other fields of study? How might the losses be \

A National Trauma Care System: Integrating Military and Civilian Trauma Systems to Achieve Zero Preventable Deaths After Injury - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
Advances in trauma care have accelerated over the past decade, spurred by the significant burden of injury from the wars in Afghanistan and Iraq. Between 2005 and 2013, the case fatality rate for United States service members injured in Afghanistan decreased by nearly 50 percent, despite an increase in the severity of injury among U.S. troops during the same period of time. But as the war in Afghanistan ends, knowledge and advances in trauma care developed by the Department of Defense (DoD) over the past decade from experiences in Afghanistan and Iraq may be lost. This would have implications for the quality of trauma care both within the DoD and in the civilian setting, where adoption of military advances in trauma care has become increasingly common and necessary to improve the response to multiple civilian casualty events. Intentional steps to codify and harvest the lessons learned within the military's trauma system are needed to ensure a ready military medical force for future combat and to prevent death from survivable injuries in both military and civilian systems. This will require partnership across military and civilian sectors and a sustained commitment from trauma system leaders at all levels to assure that the necessary knowledge and tools are not lost. A National Trauma Care System defines the components of a learning health system necessary to enable continued improvement in trauma care in both the civilian and the military sectors. This report provides recommendations to ensure that lessons learned over the past decade from the military's experiences in Afghanistan and Iraq are sustained and built upon for future combat operations and translated into the U.S. civilian system.